Risk Factors and Infection Patterns of Patients with Nephrotic Syndrome Attending a Tertiary Level Hospital: An Update (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Nephrotic syndrome (NS) is one of the most common childhood kidney diseases where defective immune systemincreases the chances of various infections. Forecasting the prognosis and proper planned management based on therecent data of risk factors and infection patterns can reduce the associated morbidities and mortalities. Weinvestigated the incidences of infection and associated risk factors among the hospitalized children to provide anupdated view of the current infection pattern of children with NS. This observational study was conducted at theDepartment of Pediatrics, Bangabandhu Sheikh Mujib Medical College Hospital, Bangladesh, from July 2017 to June2020. A total of 167 children aged